LEADERSHIP AND LEARNER DISCIPLINE IN JOHANNESBURG NORTH DISTRICT SCHOOLS. - Makibela, Matshweni Bennette (My University, 2014)
During the period of 2010 to 2012, the statistics collected by the Gauteng Department of Education revealed that there was a growing number of reported queries to the education authorities in as far as learner discipline was concerned. These cases showed a wide range of learner misconduct which was most prevalent in the former Model C schools than in the Township schools. The interesting part of some of the research findings was that those schools which were up in arms to deal with issues of learner misconduct were performing much better than their counterparts in the townships in the academic sphere. This makes school leadership in township schools questionable. The other aspect that was investigated was the manner in which those queries were handled to ensure procedural fairness as well as substantive fairness. This study was to elicit a correlation between leadership and learner discipline as well as the reason why schools that have more reported cases of learner misconduct are having better academic performance than those institutions that have few or no reported queries to the education authorities. There was also an issue of a dearth of leadership that emerged as some of the township schools lacked capacity in dealing with such issues which resulted in them avoiding to deal with such conflict situations. A literature study and empirical investigation were conducted to determine factors affecting learner discipline, the role of leadership in dealing with learner discipline and why there are more reported incidences of learner misconduct in the former model C schools than in the township schools.
MM (P&DM) thesis
Keywords: Leadership in schools; Learners; Discipline in schools